Soil Contamination by Metals/Metalloids around an Industrial Region and Associated Human Health Risk Assessment - Hale Demirtepe (Journal of Advanced Research in Natural and Applied Sciences)
Industrial, agricultural, transportation, and waste management activities cause soil contamination by metals/metalloids. Soil contamination is an essential global concern since it poses a significant risk to human health. Particularly in areas near heavy industry, people are more prone to exposure. This study aims to determine current metal/metalloid contamination levels in soil from Aliağa industrial region and assess associated health risks. Five surface soil samples were collected from the region, representing residential, agricultural areas, and downwind of possible sources. Pollution indices were calculated to determine the metal(loid)s with anthropogenic inputs, and a human health risk assessment was conducted. As a result, significant to extreme enrichment of arsenic (As), moderate to significant enrichment of zinc (Zn) and manganese (Mn), and very high enrichment of lead (Pb) and cadmium (Cd) were observed in soil samples. Possible sources of contamination were iron and steel facilities with electric arc furnaces and oil combustion. Non-carcinogenic risk assessment revealed acceptable risks of exposure to Aliağa soils, while exposure scenarios had a great impact on estimated risks. Arsenic, chromium (Cr), and Pb appeared to be significant contributors to non-carcinogenic risk. Carcinogenic risks associated with exposure to As, Pb, Cr, cobalt (Co), and Cd in soils were evaluated to be at an acceptable level. This study only considered soil exposure pathways; hence, a comprehensive risk assessment is deemed necessary not to underestimate the risk of living around an industrial region. Nevertheless, the study provided crucial information for the current hot spots for metal(loid)s in the region and human exposure level.